PENGARUH THERAPEUTIC EXERCISE WALKING TERHADAP KUALITAS TIDUR KLIEN DENGAN PENYAKIT PARU OBSTRUKSI KRONIK (PPOK) DI RS TK II PUTRI HIJAU MEDAN - Elis Anggeria (Universitas Prima Indonesia, 2018)
PPOK becomes the first rank in the group of lung diseases in Indonesia, followed by bronchial asthma, lung cancer and other lung diseases. Therapeutic exercise is an action of running regular walking with hands swayed to the rhythm of the road, this action is excellent for all age levels in order to improve the quality of sleeping. The research aims to find out the effect of therapeutic walking exercise in patients with chronic obstructive pulmonary disease in TK II Putri Hijau Medan Hospital Medan.This research used an experimental desgin by the use of quasi experimental design through pre-test and post-test paired t-test group. The research population were 9 people, and the sampling technique used in this study is saturation sampling technique by taking the entire population as samples. There is the mean difference between pretest and posttest on sleep quality by 0.56, meaning that the average quality of sleep on posttest have a better category than the average quality of sleep on pretest, which means therapeutic exercise of walking affects quality of sleep in patients with chronic obstructive pulmonary disease with p-value of 0,013. There isa a significant effect of therapeutic exercise of walking on sleep quality. Therapeutic exercise of walking is form of therapy that is proven to improve sleep quality, therefore, is expected that patients can perform therapeutic exercise of walking guided by nurses.